Development of a Safety Evaluation Model for Provincial Highway - Li Yuan; He-wei Yuan; Yong-feng Ma; Ying-wei Ren (Discrete Dynamics in Nature and Society)
Provincial highway safety is one of the most important issues in transportation. To evaluate or assess the safety performance of provincial highway, traffic crash analysis or traffic conflict analysis has been used for a long history. However, it is very difficult and time-consuming to obtain historical crash data or traffic conflict data. This study analyzes the provincial highways' accident data during 2006–2010, and the characteristics of provincial highway have been investigated; in addition the influencing elements are identified. A comprehensive approach is introduced to evaluate provincial highway safety performance and corresponding models are developed considering the accidents, geometrics, facilities, and traffic environment. The approach will also result in a safety index to indicate the safety performance level of the provincial highway. In this paper, the approach (called safety evaluation approach) is practically applied to evaluate the safety performance of some provincial highways in Hebei Province. Results from the real application indicate that the approach has good applicability and can be used by field safety engineers.